Creating an Empathetic Board: The Power of Feeling "Gotten". Issue 142 (November 2015) - Zubizarreta, Rosa
Abstract : Board members need to collaborate in order to arrive at collective decisions, and it isn't always easy. Here, Rosa Zubizarreta of Diapraxis, which specializes in collaborative leadership and "flow‐friendly meetings, " provides some insights to help boards develop the empathetic approach that is crucial to this work.